A compact and optimized liquid-cooled thermal management system for high power lithium-ion capacitors. (25th February 2021) - Karimi, Danial; Behi, Hamidreza; Hosen, Md Sazzad; Jaguemont, Joris; Berecibar, Maitane; Van Mierlo, Joeri
Highlights: A liquid-based thermal management system (TMS) is proposed to enhance the cooling and temperature uniformity of a prismatic high-power lithium capacitor (LiC) cell. The monitored temperature under natural convection, forced convection, and liquid-based TMS was recorded as 55.7 °C, 44.8 °C, and 32.6 °C, respectively. A numerical model is developed to help the visualization of the temperature. The inlet flow rate of 100 mL/min, and 3 mm channel diameter are the optimal considerations, considering the cost, weight, and volume. Abstract: Designing a proper thermal management system (TMS) is indispensable to the energy storage systems (ESS) of electric vehicles for reliability and safety. The high heat transfer rate and low power consumption of liquid cooling systems made them a perfect candidate amongst various TMS. Nonetheless, the compactness of the liquid cooling TMS has paid less attention in the literature, which plays a vital role in the specific energy of ESSs. In this study, a liquid-based TMS is designed for a prismatic high-power lithium-ion capacitor (LiC). The proposed TMS integrates a LiC cell surrounded by two cooling plates through which coolant fluid flows into serpentine channels. This study aims to explore factors that affect the temperature contour and uniformity of the battery. Experimental tests have been conducted to investigate the effect of inlet coolant temperature and inlet coolant flow rate. As the gap filler eliminates the air gap barrier between the cell and cooling plates, the impact of the selected thermal interface material (TIM) is also studied. Besides, the number of arcs of the channels in the coolant path and the channel diameter is investigated in the optimization section. The experimental results revealed that the monitored temperature in three cases of natural convection, forced convection, and liquid-based TMS was recorded as 55.7 °C, 44.8 °C, and 32.6 °C, respectively. The optimization results proved that by increasing the inlet coolant temperature from 23 °C to 30 °C, the temperature sensed by the thermocouple increases by 11.5%. Also, by increasing the inlet flow rate from 100 mL/min to 200 mL/min, the temperature declines from 32.6 °C to 31.5 °C; hence, to avoid higher power consumption and pressure drop, the main flow rate of 100 mL/min is preferred.